2019
DOI: 10.1055/a-0582-8040
|View full text |Cite
|
Sign up to set email alerts
|

Kniegelenknahe Korrekturosteotomien

Abstract: ZusammenfassungKniegelenknahe Korrekturosteotomien bei unikompartimenteller Gonarthrose haben in den letzten Jahren eine starke Renaissance erlebt. Sie müssen als Alternative zum monokompartimentellen oder kompletten Gelenkersatz mit bedacht werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
(16 reference statements)
0
7
0
1
Order By: Relevance
“…Der HSS-Score (präoperativ: 69,5 ; Follow-up: 71 [56-86]; p = 0,6941) zeigte keine signifikante Veränderung über den 10-Jahres-Beobachtungszeitraum. Der Lequesne-Score war signifikant niedriger als präoperativ (präoperativ: 11,5 [0, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]; Follow-up: 7 [1][2][3][4][5][6][7][8][9][10][11][12][13]; p < 0,001), was einer geringeren Einschränkung entspricht. Schlussfolgerungen Für die Mehrheit der Patienten mit medialer Gonathrose, die eine Behandlung mittels HTO und Stabilisierung durch eine Tomofix-Platte erhalten, kann erwartet werden, dass mindestens 10 Jahre keine Implantation einer KTP notwendig wird.…”
Section: Zusammenfassungunclassified
See 3 more Smart Citations
“…Der HSS-Score (präoperativ: 69,5 ; Follow-up: 71 [56-86]; p = 0,6941) zeigte keine signifikante Veränderung über den 10-Jahres-Beobachtungszeitraum. Der Lequesne-Score war signifikant niedriger als präoperativ (präoperativ: 11,5 [0, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]; Follow-up: 7 [1][2][3][4][5][6][7][8][9][10][11][12][13]; p < 0,001), was einer geringeren Einschränkung entspricht. Schlussfolgerungen Für die Mehrheit der Patienten mit medialer Gonathrose, die eine Behandlung mittels HTO und Stabilisierung durch eine Tomofix-Platte erhalten, kann erwartet werden, dass mindestens 10 Jahre keine Implantation einer KTP notwendig wird.…”
Section: Zusammenfassungunclassified
“…Medial open wedge high tibial osteotomy (HTO) is a widespread and commonly accepted surgery to avoid or delay unicompartmental or total knee arthroplasty (TKA) in patients with medial compartment knee osteoarthritis (OA) and varus malalignment [1,2]. Several mid-to long-term clinical studies have reported good to excellent clinical results demonstrating improvements in quality of life and a high rate of return to sports [3,4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanical and anatomical principles of osteotomy are of great concern in order to achieve appropriate alignment and joint congruency after surgery [ 8 , 9 ]. The most frequently performed osteotomy is the medial open-wedge high tibial osteotomy (HTO), which is for the treatment of early stage osteoarthritis [ 10 ], and the tibial tubercle osteotomy (TTO), which is for recurrent patella dislocation or patellofemoral arthritis [ 11 ]. Additionally, osteotomies are of common use during total knee arthroplasty (TKA): TTO as an approach for revision surgery or epicondylar osteotomy for TKA balancing [ 12 ].…”
Section: Introductionmentioning
confidence: 99%